PENINGKATAN KOMPETENSI ANALISIS DATA MAHASISWA MELALUI PELATIHAN SPSS DI UNIVERSITAS DINAMIKA - S Sulistiowati; Bambang Hariadi; Julianto Lemantara; Januar Wibowo; Hardman Budiardjo (Jurnal AbdiMas Nusa Mandiri, 2026)
Data processing and analysis skills are essential competencies for students in supporting research activities, particularly questionnaire-based quantitative research. This community service activity aimed to improve the competency of first-semester students in processing and analyzing data using the SPSS application. A total of 300 students participated in the training, which was conducted through lectures, question-and-answer sessions, discussions, and hands-on practice based on questionnaire case studies. Evaluation was carried out using pre-tests and post-tests, and the data were analyzed using the Kolmogorov–Smirnov normality test and the Paired Samples t-test. The results indicated that the data were normally distributed and that there was a significant improvement in students' competencies after the training. Quantitatively, students' competencies increased by 46.8% compared with their pre-training performance. These findings indicate that SPSS training is effective in improving students' data analysis competencies and supporting research readiness from the early stages of higher education.